How outstanding leaders lead with affect: An examination of charismatic, ideological, and pragmatic leaders - Griffith, J.; Connelly, S.; Thiel, C.; Johnson, Genevieve (2015)
Frameworks for understanding outstanding leadership have flourished in the past decade. Research into the charismatic, ideological, and pragmatic (CIP) model of leadership in particular has examined how leaders develop mental models, frame visions, communicate goals, and utilize political tactics to form relationships with followers and impact society in meaningful ways. However, a discussion of how these types of leaders use emotions and influence tactics to influence followers and affect society is notably absent in the literature. To fill this gap, the current effort focuses on how charismatic, ideological, and pragmatic leaders differ in their use of emotional displays and influence tactics. Results suggest that the emotional displays and influence tactics that leaders use successfully discriminate between CIP leader types and create expected leader styles. Implications of these findings are also discussed.